2019
DOI: 10.3390/ani9090691
|View full text |Cite
|
Sign up to set email alerts
|

Validation Study of SNPs in CAPN1-CAST Genes on the Tenderness of Muscles (Longissimus thoracis and Semimembranosus) in Hanwoo (Korean Cattle)

Abstract: Simple SummaryFor meat tenderness, single nucleotide polymorphisms (SNPs) in the μ-calpain (CAPN1) and calpastatin (CAST) genes have been reported to be associated with Warner-Bratzler shear force (WBSF) in different cattle populations, including Korean Hanwoo cattle. In this study, we validated the association of seven SNPs in CAPN1 and CAST genes with meat tenderness in two different muscle cuts tenderness in the Longissimus thoracis (LT) and Semimembranosus (SM) muscles. Two SNPs in CAPN1 and one SNPs in CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…About 13 SNPs significant for tenderness were located in a 3 cM region around CAPN1. Moreover, some studied related to the CAPN1 gene had been reported in some cattle (Xin et al, 2011;Sun et al, 2018;Lee et al, 2019), and previous studies had been reported in the same markers in different animal populations in sheep (Machado et al, 2020;Aviles et al, 2013), Pig (Ropka-Molik et al, 2017), and chicken (Shu et al, 2015;Anaas et al, 2016). However, it was limited studied about the non-coding in the 3'UTR region of CAPN1 gene, especially in Bali cattle.…”
Section: Introductionmentioning
confidence: 85%
“…About 13 SNPs significant for tenderness were located in a 3 cM region around CAPN1. Moreover, some studied related to the CAPN1 gene had been reported in some cattle (Xin et al, 2011;Sun et al, 2018;Lee et al, 2019), and previous studies had been reported in the same markers in different animal populations in sheep (Machado et al, 2020;Aviles et al, 2013), Pig (Ropka-Molik et al, 2017), and chicken (Shu et al, 2015;Anaas et al, 2016). However, it was limited studied about the non-coding in the 3'UTR region of CAPN1 gene, especially in Bali cattle.…”
Section: Introductionmentioning
confidence: 85%
“…These traits are influenced by several factors, including breed, genetic, age, management, feeding regime, and growth stages [ 24 ]. Moreover, in efforts to improve meat quality, earlier studies have focused on the detection of key genes along with a precise understanding of the underlying biology of quantitative traits to better meet consumer expectations [ 1 , 25 , 26 , 27 , 28 ]. Hence, the screening of potential candidate genes to comprehend the connection between gene variations and back fat thickness and intramuscular fat is necessary.…”
Section: Candidate Genes Affecting Back Fat Thickness and Marbling Scorementioning
confidence: 99%
“…It was shown that the serine/threonine substitution (S20T) in the CAST gene is connected to carcass traits in Simmental cattle [ 96 ]. Moreover, the associations of seven SNPs in CAPN1 and CAST genes with meat tenderness have previously been reported in two different muscle cuts in Hanwoo cattle [ 25 ]. LEP and LEPR genes were identified as promising candidate genes responsible for increasing weight, growth traits [ 106 , 107 ], energy storage [ 106 , 108 ], and lipid metabolism [ 109 ].…”
Section: Candidate Genes Affecting Eye Muscle Areamentioning
confidence: 99%
“…However, these authors did not observe a significant association with some of the evaluated traits, such as marbling score and shear force. Lee et al (2019) evaluated the association of three SNPs in the CAST gene (exon 7) with meat tenderness in two muscle cuts (longissimus thoracis and semimembranosus) from Hanwoo steers and observed the following SNPs: G>A, G>A and G>C; these SNPs were significantly related to increased shear force in both muscles. Also is reported association of shear force of longissimus muscle in Australian cattle with c.28i2A>G polymorphism of gene CAST (CAST2832) by Bolormaa et al (2011).…”
mentioning
confidence: 99%